Physical Activity and Obesity in Canadian Women - Walsh Peter; Bryan Shirley (BMC, 2004)
Abstract Health Issue Overweight and obesity have been recognized as major public health concern in Canada and throughout the world. Lack of physical activity, through its impact on energy balance, has been identified as an important modifiable risk factor for obesity. Physical activity and obesity are also important risk factors for a variety of chronic diseases. This chapter provides an overview of the current state of physical activity and overweight/obesity among Canadian women. Key Findings For all ages combined more women (57%) than men (50%) are physically inactive (energy expenditure <1.5 KKD). Physical activity increases as income adequacy and educational level decrease. Physical inactivity also varies by ethnicity. The prevalence of both overweight (BMI 25.0 - 29.9 kg/m2) and obese (BMI ≥ 30 kg/m2) Canadian women has increased 7% since 1985. Obesity increases with age and is highest among women reporting low and lower middle incomes and lower levels of education. The prevalence of obesity is highest among Aboriginal women and men (28% and 22% respectively). Data Gaps and Recommendations There is currently no surveillance system in Canada to monitor the level of physical activity among children, those performing activity at work, at school or in the home. There is a gap in the knowledge surrounding socio-cultural and ecological determinants of physical activity and obesity and the associations of these to chronic disease among women and minority populations. Multi-sectoral policy interventions that act to decrease the broad systemic barriers to physical activity and healthy weights among all women are needed.